Blue‐Emissive Cobalt(III) Complexes and Their Use in the Photocatalytic Trifluoromethylation of Polycyclic Aromatic Hydrocarbons. Issue 27 (4th June 2018) - Pal, Amlan K.; Li, Chenfei; Hanan, Garry S.; Zysman‐Colman, Eli
Abstract: Room‐temperature luminescent Co III complexes (1 and 2 ) are presented that exhibit intense ligand‐to‐metal and ligand‐to‐ligand charge transfer absorption in the low‐energy UV region ( λ abs ≈360–400 nm) and low‐negative quasi‐reversible reduction events ( E 1/2 (red) =−0.58 V and −0.39 V vs. SCE for 1 and 2, respectively). The blue emission of 1 and 2 at RT is due to the large bite angles and strong σ‐donation of the ligands, the combined effect of which helps to separate the emissive 3 LMCT (triplet ligand‐to‐metal charge transfer) and the non‐emissive 3 MC (triplet metal‐centered) states. 1 and 2 were found to be powerful photo‐oxidants ( E Co III * / Co II =2.26 V and 2.75 V vs. SCE of 1 and 2, respectively) and were used as inexpensive photoredox catalysts for the regioselective mono(trifluoromethylation) of polycyclic aromatic hydrocarbons (PAHs) in good yields (ca. 40–58 %). Abstract : Reduction 'n' blues : Room‐temperature blue‐emissive Co III complexes were synthesized. The low negative first reduction potential and the high excited‐state energies made them strong photo‐oxidants. They are successfully adapted in the photoredox trifluoromethylation of polycyclic aromatic hydrocarbons (PAHs).